PENERAPAN AGILE DEVELOPMENT METHODS DENGAN FRAMEWORK SCRUM PADA PERANCANGAN PERANGKAT LUNAK KEHADIRAN RAPAT UMUM BERBASIS QR-CODE - KM. Syarif Haryana (Jurnal Computech & Bisnis (e-Journal), 2019)
Software is the backbone of business processing in all aspects that require automation. Software Development must be supported by choosing the right Software Development Method. Many methods can be chosen by the user, but most of the methods used were 20 to 30 years ago, so they do not meet current needs. In this research, software development using Agile Development Methods with the chosen model is SCRUM, where the software development methodology is based on the same principles and is a short-term system development that requires rapid adaptation from developers to changes in any form. As the object of implementation in this study, the trial was applied to the case of the Application of Attendance at the QR-Code-based General Meeting. Keyword : Software, Application, Presence, QR-CodeDOI : http://doi.org/10.5281/zenodo.3631045